Strong direct exchange coupling and single-molecule magnetism in indigo-bridged lanthanide dimers. Issue 21 (28th February 2017) - Guo, Fu-Sheng; Layfield, Richard A.
Abstract : The first lanthanide–indigo complexes are described, including a dysprosium single-molecule magnet and one of the strongest exchange coupling constants measured in a gadolinium compound. Abstract : The synthesis, structure and magnetic properties of the indigo-bridged dilanthanide complexes [(η 5 -Cp*)2 Ln2 (μ-ind)] n − with Ln = Gd or Dy and n = 0, 1 or 2 are described. The gadolinium complexes with n = 0 and 2 show typically weak exchange coupling, whereas the complex bridged by the radical [ind] 3− ligand shows an unusually large coupling constant of J = −11 cm −1 (−2 J formalism). The dysprosium complexes with n = 0 and 1 are single-molecule magnets in zero applied field, whereas the complex with n = 2 does not show slow magnetic relaxation.